Studies on the Influence of Temperature in Aquatic Anuran Population in Cauvery Delta Region of Tranquebar Taluk of Nagapattinam District, Tamil Nadu, India: Studies on the Influence of Temperature in Aquatic Anuran Population in Cauvery Delta Region of Tranquebar Taluk of Nagapattinam District, Tamil Nadu, India - Karunakaran, K. (International Journal of Pharmaceutical & Biological Archive, 2019)
Amphibian is one of the important ecosystem component, both the ecologically and economically. In the present study, we intended to analyze the population density based on the temperature in different months during the year 2016–2017. The data were collected by visual encounter survey method ,and amphibians were recorded in all 12 months from the study area for 2 years. The monthly variation habitat temperature was recorded in 2016–2017 using analysis of variance. In different habitat (cultivable, non-cultivable, pond, and grassland) temperature, the population was maximum at pond followed by grassland, agriculture, and non-cultivable. The maximum temperature was found in July with 74 numbers of species which were identified during 2016. Were recorded high number (1600) frog were recorded in pond 28°C during samba season followed by Thaladi and Kuruvai. Based on this study, we conclude that the population density may increase and decrease based on the temperature in all the three seasons with four microhabitats.